1988
DOI: 10.1530/jrf.0.0830273
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of melatonin on sexual maturation in female rats

Abstract: Daily subcutaneous injections of 100 \ g=m\ g melatonin given to prepubertal female rats housed in 14L:10D or 12L:12D failed to delay puberty as evidenced by the age at which vaginal opening occurred; neither the Sprague\p=n-\Dawley nor the Wistar strain rats were responsive to melatonin treatment. Reproductive organ weights (ovaries and uteri) at vaginal opening were unaffected by such treatment. Administration of melatonin through the drinking water in doses of 100, 500 or 1000 \g=m\g/day did not alter the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Rivest et al (1985) injected melatonin into female Wi star rats from Swiss colonies and found a 10-day delay in vaginal opening. The effect was not replicated in another study in which rats from North American colonies were used (Badawi and Wilkinson, 1988).…”
Section: Mammalsmentioning
confidence: 87%
See 1 more Smart Citation
“…Rivest et al (1985) injected melatonin into female Wi star rats from Swiss colonies and found a 10-day delay in vaginal opening. The effect was not replicated in another study in which rats from North American colonies were used (Badawi and Wilkinson, 1988).…”
Section: Mammalsmentioning
confidence: 87%
“…Rivest et al (1985) injected melatonin into female Wi star rats from Swiss colonies and found a 10-day delay in vaginal opening. The effect was not replicated in another study in which rats from North American colonies were used (Badawi and Wilkinson, 1988).Rats and other nocturnal mammals appear to be much more sensitive to light intensity than humans. Fluorescent light below 5 lux intensity resulted in a 50% reduction in SNAT activity in rats (Minneman et al, 1974).…”
mentioning
confidence: 91%
“…In contrast, some researchers (Badawi and Wilkinson, 1988) have declared that daily injections of MT, at the appropriate time, in appropriate dose under controlled temperature and lighting arrangements failed to delay puberty, irrespective of the colony of rats used. As a matter of fact, Badawi and Wilkinson (1988) found that the vaginal opening was significantly advanced by 1.5 days. In our experiment, 5-day-old rats treated with MT for 10,15, and 20 days all had a VOD earlier than their corresponding control rats with values ranging from 2.67-7 days, which are all statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…The low levels of mela tonin at the time of sexual maturation in the female rabbit 100-120 days of age [9,10,22] also provides similar presumptive evidence. The question arises as to whether the pre sumptive high pineal gland activity on days 72-91 plays a role in inducing puberty, and would be contradictory to previous evidence indicating that melatonin delays puberty in the rat [23][24][25][26], On the other hand, more recent data failed to show an effect of mela tonin on puberty in the female rat [25] but increased LH pulse amplitude in women [27], High melatonin levels have been associated with infertility [28,29]. If high melatonin causes infertility by inducing a sustained in crease in LH pulse amplitude without appro priate negative feedback from the gonads, one would expect a delay in puberty.…”
Section: Discussionmentioning
confidence: 99%